Strengthening the Character of Young Children Based on Banjar Ethnic Parenting - Tria Valentina Wahyudanti; Fachrul Rozie; Evie Palenewen; Fitri Anjarwati (Poltanesa, 2025)
The Banjar ethnic group is one of the ethnic groups in Indonesia. Rich in traditions, cultural values, and customs, the Banjar ethnic group applies a parenting style that emphasizes religious, social, and independence aspects. In this study, the researcher found parenting practices among the Banjar ethnic group that emphasize religious aspects in educating children from an early age and habituation in worship practices. The participants in this study were a family consisting of a father, mother, and three children. This study focused on developing a typology of parenting and the values of ethno-parenting of parents based on the Banjar ethnicity. This was supported by the results of direct interviews, observations, and document studies conducted by researchers on parenting practices among the Banjar ethnic group living in Samarinda. The purpose of this article is to present information related to strengthening the character of early childhood based on the Banjar ethnic parenting pattern. This study uses a qualitative descriptive method that refers to the concept of strengthening the character of early childhood based on the Banjar ethnic parenting pattern in the internalization of worship in children from an early age. This study shows that strengthening the character of early childhood is based on daily habits.